Peran Dan Faktor Penghambat Dalam Penegakan Hukum Terhadap Pidana Pemerkosaan Oleh Anggota Keluarga Di Wilayah Hukum Kepolisian Resor Kupang Kota - Benu, Geraldo Yoseprinus; Leo, Rudepel Petrus; Amalo, Heryanto (Law Faculty, Nusa Cendana University, 2024)
Home should be the safest place for girls, but instead it is the safest location for perpetrators who carry out devious acts. The rape case committed by a family member occurred in the jurisdiction of the Kupang City Police. ADR was a victim of sexual intercourse and sexual violence with SDR's biological father from July 2004 to April 2014, causing a lot of suffering for the victim, both physical and psychological. Following the main duties of the Indonesian National Police as regulated in Article 13 of Law Number 2 of 2002. Bareskrim Polri as a government institution is the most appropriate institution to answer problems regarding the effectiveness of the role of the police. Investigators and the obstacles investigators face. The police force in enforcing the law against criminals was designed by family members at the Kupang City Police. The results of the research show that the effective role of a police investigator is the role expected by the investigator, the role given and the role of the police investigator. Obstacles to law enforcement for perpetrators of criminal acts of fraud by family members are: legal factors, law enforcement, means and facilities, and culture. It was concluded that the effective role of Kupang City Police investigators' duties is: Receiving reports, Investigation, Collection of evidence, Examination of witnesses and victims, Coordination with related parties and Assistance to victims. Meanwhile, the obstacles faced are community factors and cultural factors.